The Cultural Intelligence Scale (CQS): A Contribution to the Italian Validation - Gozzoli, Caterina; Gazzaroli, Diletta (Frontiers in Psychology, 2018)
In the current globalized working context, professionals are asked to be able to implement specific competences. Cultural Intelligence is a construct referring to an individual’s ability to function and manage effectively in culturally diverse settings and is conceived as an aggregate multidimensional construct. Purpose of this study was to examine the validity of score interpretations of the Italian version of the Cultural Intelligence Scale (CQS). CQS is aimed to measure individual ability to understand, act and manage effectively in culturally diverse settings. Participants were 755 professionals (females = 64.2%) from different organizational contexts, ranging from 20 to 63 years old (M = 40.4; SD = 10.29). Data were collected with the Italian translated version of the CQS. Results of confirmatory factor analysis suggested good data-model fit. As proposed in the original version, CQS is composed of 20 items and 4 different theoretical dimensions (Metacognitive, Cognitive, Motivational, Behavioral) that correlate with each other. This study could be considered a first contribution to fill the lack of self-report measure concerning cultural intelligence in the Italian context with a scale showing promising results.